A high-resolution study of mesospheric fine structure with the Jicamarca MST radar - Sheth, R. (2006)
Correlation studies performed on data from recent mesospheric experiments conducted with the 50-MHz Jicamarca radar in May 2003 and July 2004 are reported. The study is based on signals detected from a combination of vertical and off-vertical beams. The nominal height resolution was 150 m and spectral estimates were obtained after ~1 min integration. Spectral widths and backscattered power generally show positive correlations at upper mesospheric heights in agreement with earlier findings (e.g., Fukao et al., 1980) that upper mesospheric echoes are dominated by isotropic Bragg scatter. In many instances in the upper mesosphere, a weakening of positive correlation away from layer centers (towards top and bottom boundaries) was observed with the aid of improved height resolution. This finding supports the idea that layer edges are dominated by anisotropic turbulence. The data also suggests that negative correlations observed at lower mesospheric heights are caused by scattering from anisotropic structures rather than reflections from sharp vertical gradients in electron density.